8세 이상의 근성 사경 환자의 치료에 있어서 무세포 진피 기질의 사용 - 국경훈 (The Graduate School, Ajou University, 2017)
Background: Treatment for neglected or recurred congenital musculartorticollis should be differentiated from primary patients dueto the long-standing adjacent tissue contracture. The aim of thisstudy was to evaluate the effect of acellular dermal matrix (ADM)on surgery of recurred and neglected patients of congenital musculartorticollis. Methods: Forty-nine patients were included in the study.All patientsunderwent resection at the distal end of the sternocleidomastoidmuscle. In the study group of 18 patients (ADM group), the defectcaused bymyectomyand scar tissue removal was covered withADM.Passive range of neck motion, head tilt, cosmetic and functionalsatisfaction, and scar was evaluated and compared with the controlgroup of 31 patients (non-ADM group) during follow-up. Logisticand linear regression analyses with adjustment by propensity scorewere performed to determine the association between ADMimplantation and postoperative variables. Results: The mean follow-up period was 18.8 months. No patientrequired further operation for recurrence during follow-up. Theimprovement of neck motion in ADM group was significantlysuperior to non-ADM group at the 1-year follow-up, and theoverall assessment score was significantly higher in the ADMgroup. Acellular dermal matrix implantation was not associatedwith increased discharge of total drain. Conclusions: In patients over 8-years-of-age with recurred orneglected congenital muscular torticollis, use of dermal substituteto fill the defect caused by torticollis release is effective inachieving satisfactory neck motion. Surgical sectioning of thesternocleidomastoid muscle and ADM graft should be consideredin recurred and neglected torticollis.
학위논문(석사)--아주대학교 일반대학원 :의학과,2017. 2
Keywords: Acellular dermal matrix; congenital musculartorticollis; neglected torticollis; recurred torticollis